2016
DOI: 10.1111/nmo.12832
|View full text |Cite
|
Sign up to set email alerts
|

Prucalopride induces high‐amplitude propagating contractions in the colon of patients with chronic constipation: a randomized study

Abstract: Key Points• The aim of this study was to compare the effects on colonic motility of prucalopride vs polyethylene glycol 3350 + electrolytes (PEG3350) in patients with chronic constipation (n = 12).• The primary endpoint was the number of high-amplitude propagating contractions (HAPCs), which were measured using colonic manometry catheters.• In the 12-h period following treatment, a significant increase in HAPCs (p < 0.05) was observed in patients treated with prucalopride compared with those receiving PEG3350.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
22
1
1
Order By: Relevance
“…In particular, prucalopride, used by Shokrollahi et al to demonstrate prokinetic effects on propulsive motor patterns in rabbit proximal colon, has emerged as a popular and effective therapeutic agent for promoting gut motility. Prucalopride displays high‐affinity binding to human 5‐HT 4(a) and 5‐HT 4(b) receptor isoforms which is consistent with its clinical success since these isoforms are expressed in the human colon (Table ). Other high‐affinity agonists have also been developed including naronapride (ATI‐7505), velusetrag (TD‐5108), and YH12852.…”
Section: ‐Ht4rs and Prokinetic Agentsmentioning
confidence: 52%
See 1 more Smart Citation
“…In particular, prucalopride, used by Shokrollahi et al to demonstrate prokinetic effects on propulsive motor patterns in rabbit proximal colon, has emerged as a popular and effective therapeutic agent for promoting gut motility. Prucalopride displays high‐affinity binding to human 5‐HT 4(a) and 5‐HT 4(b) receptor isoforms which is consistent with its clinical success since these isoforms are expressed in the human colon (Table ). Other high‐affinity agonists have also been developed including naronapride (ATI‐7505), velusetrag (TD‐5108), and YH12852.…”
Section: ‐Ht4rs and Prokinetic Agentsmentioning
confidence: 52%
“…Notwithstanding these complexities, clinical studies in humans and many pharmacological studies in isolated preparations in small animals reveal a common theme: 5‐HT 4 Rs initiate and/or enhance peristaltic reflexes and/or propulsion. This has been demonstrated in guinea pig ileum and colon, mouse, rat and dog colon, and human jejunum and colon . Use of early 5‐HT 4 R agonists in humans including cisapride, mosapride, and tegaserod was limited by their adverse secondary effects on other systems following their systemic absorption.…”
Section: ‐Ht4rs and Prokinetic Agentsmentioning
confidence: 99%
“…Several of the agents evaluated in this network meta-analysis accelerate colonic transit, including intestinal secretagogues (lubiprostone,37 linaclotide,38 and the bile acid transport inhibitor, elobixibat39) and prokinetic agents (prucalopride,40 tegaserod,41 and bisacodyl42). However, among all these drugs, only prucalopride43 and bisacodyl have been shown to increase the number of high amplitude propagated contractions, which are highly propulsive in the colon 44. Lubiprostone did not induce colonic high amplitude contractions 45…”
Section: Discussionmentioning
confidence: 99%
“…31 In a more recent study, prucalopride was shown not only to increase frequency of giant or high-amplitude contractions in the colon, but also to augment their amplitude, propagation distance and velocity; effects that were all significantly greater than those observed with polyethylene glycol (PEG) 3350 plus electrolytes. 32 Prucalopride is not extensively metabolized in the body and does not influence the function of cytochrome P450 or P glycoprotein; hence, it does not have clinically significant interactions with other drugs. 33 While prucalopride has been shown to interact with cardiac hERG potassium channels, blockade occurs only at very high concentrations; 150 times greater than the therapeutic dose.…”
Section: -Ht4 Receptor Agonists In CCmentioning
confidence: 99%
“…35 However, there were no effects on late repolarizations or the refractory period and there was no evidence of any arrhythmic activity. 35 Prucalopride: clinical evidence in chronic idiopathic constipation Based on the aforementioned effects of prucalopride on colonic motility and transit, [30][31][32] it should come as no surprise that a major clinical focus has been on its therapeutic role in constipation. Efficacy, tolerability, safety and impact on quality of life have been demonstrated in a number of large, randomized, placebo-controlled trials 36 which have led to the approval of prucalopride in several countries, with the usual recommended dose being 2 mg per day in patients under 65 years of age and 1 mg per day in patients over 65 years.…”
Section: -Ht4 Receptor Agonists In CCmentioning
confidence: 99%